The Synergy of Sustainable Tourism and Agriculture as a Factor of Regional Development Management in Croatia - Željko Turkalj; Marija Ham; Ivana Fosić (Ekonomski Vjesnik, 2013)
Adequate validation of regional areas is imperative for Croatian economy. The aim of this paper is to show that there is a strong interdependence and the potential for achieving synergistic effect between tourism and the agriculture and food industry. It is possible, through systematic marketing research and investment in operationalization of this synergy, along with an adequate evaluation of specificity and characteristics of individual regions, to exploit their strengths and even their flaws as a competitive advantage and achieve qualitatively and quantitatively stronger development of all regions in Croatia. Authors discuss tourism and the agriculture and food industry in light of symbiotic and synergistic factors in global conditions of growing environmental awareness and the prevailing concept of sustainable development as well as the role (green) marketing can and should play in the function of regional development and increasing competitiveness of regions. The conclusions are based on the analysis of the key indicators from secondary research, insights from scientific literature and available strategic documents which were confronted with the relevant trends in the global market. The paper shows that the focus on tourism and the agriculture and food industry as the fundamental pillars of development and commitment to sustainable development based on the preservation of the environment, rich natural diversity and heritage has a stronghold in objective resources and opportunities arising from internal strengths and weaknesses, as well as relevant trends in the global market.